Can unconditional cash transfers mitigate the impact of civil conflict on acute child malnutrition in Yemen?: Evidence from the national social protection monitoring survey - Ecker, Olivier; Maystadt, Jean-François; Guo, Zhe (International Food Policy Research Institute, 2019)
Hunger and acute child malnutrition are increasingly concentrated in fragile countries and civil conflict zones. According to the United Nations, Yemen’s civil war has caused the world’s worst humanitarian crisis in recent history. We use high-frequency panel data and district fixed-effects and household fixed-effects models to estimate the impact of civil conflict on child nutrition. Our results indicate that an increase by one standard deviation in civil conflict intensity translates into an increase in the prevalence of acute child malnutrition by at least 0.7 percentage points if measured by weight-for-height z-scores and by at least 1.7 percentage points if measured by mid-upper arm circumference z-scores. In mid-December 2018, Yemen’s main warring parties agreed to a ceasefire for the contested port city of Hodeida and to allow humanitarian aid to be shipped in and distributed through protected corridors. While the recent agreements are an important, first step to tackle the humanitarian crisis, the road to a sustainable peace agreement will certainly be long and bumpy. Relative stability could soon open a window of opportunity for targeted interventions to support recovery in Yemen. Against this background, our analysis suggests that unconditional cash transfers can be an effective tool in situations of complex emergencies. Our estimation results show that cash transfers can mitigate the detrimental impact of lingering civil conflict on child nutritional status in Yemen on a large scale. Our results also reveal that the regularity of transfer payments influence the magnitude of the mitigation effect, as regular assistance allows beneficiary households to smoothen their food consumption and other demands influencing child nutrition outcomes.